Lichtduschen Geschichte einer Gesundheitstechnik, 1890-1975 - Ingold, Niklaus (Chronos Verlag, 2015)
Light showers History of a Health Technology, 1890-1960 In the interwar period, western health experts considered ultraviolet light a powerful means for stimulating the population. In Germany, the electrical industry started to sell sunlamps for daily use, while hy-gienists and the spokesmen of the health reform movement celebrated the health effects of "light showers" in the popular press. Based on a careful reading of a wide variety of scientific and popular texts, the book maps the functions of sunlight in western medicine and culture. It studies the history of light and heliotherapy in medicine and inves-tigates the transition of medical practices towards a marketed con-sumer product. The book argues that the electrification of light thera-py shaped a new rationale for the application of light on the human body in medicine and beyond at the start of the 20th century.